Surface Integrity of a High Speed Milling FC300 Gray Cast Iron - Mohd, Hadzley; Nurul, Fatin; Raja, Izamshah; Hussein, Nur Izan Syahriah; Siti, Sarah; Subramonian, Sivarao (Trans Tech Publications, 2014)
High speed milling is one of the most important processes to produce tool and die based material such as difficult to cut gray cast iron grade FC300. This paper presents the results of an experimental investigation on the effect of spindle speed and feed rate in high speed milling of FC300 gray cast iron with 32mm diameter uncoated carbide cutting tools. Milling tests were carried out under dry condition at four different spindle speeds, 6000, 7000, 8000 and 9000 rpm and four different feed rates, 4m/min, 5m/min, 6m/min and 9m/min. Surface integrity was analyzed based on the cross sectional observation beneath the machined surface. The results shows that the increasing spindle speed and feed rate significantly alter the grain structure of FC300, around 2um-25um beneath the machined surface. Observation from SEM shows some evidence of grain bending, thus reflecting the high ductility formation of FC300 due to the high temperature generation, high shearing force and high friction generated during machining. Milling under 6000 rpm spindle speed and 4m/min feed rate produced minimum effect of surface deformations.